Work, teacher training, and integration of DICT to educational practices: Beyond technological rationality - Marfim, Lucas; Pesce, Lucila (Education Policy Analysis Archives, 2019)
As a result of an academic research integrated with an interinstitutional research, this article is a theoretical-conceptual study, which discusses how the development and spread of technology, under the capitalist mode of production and conditioned by its own rationality, are a part of a global model of power organization that drive human training purposes and decisively affect current public educational policies for teacher work and training. The text also highlights and problematizes the contradictions related to the sociocultural and economic transformations caused by the emergence of digital information and communication technologies (DICT) to discuss the limits and possibilities of integrating DICT with pedagogical practices, considering their educational implications, under ethical approach, so that this field of training of graduates goes beyond the technical parameters linked to economic productivity. As a result of an academic research integrated with an interinstitutional research, this article is a theoretical-conceptual study, which discusses how the development and spread of technology, under the capitalist mode of production and conditioned by its own rationality, are a part of a global model of power organization that drive human training purposes and decisively affect current public educational policies for teacher work and training. The text also highlights and problematizes the contradictions related to the sociocultural and economic transformations caused by the emergence of digital information and communication technologies (DICT) to discuss the limits and possibilities of integrating DICT with pedagogical practices, considering their educational implications, under ethical approach, so that this field of training of graduates goes beyond the technical parameters linked to economic productivity.